Prognosis of complications of acute brucellosis from hepatobiliary and cardiovascular systems - Elchin Huseynov Mammad oglu (Kazimierz Wielki University, 2019)
Brucellosis is a worldwide spread bacterial zoonosis, causing the globality of the problem. Brucellosis is a systemic disease with a wide range of clinical features that can cause pathological changes in any organ of the human body. The purpose of our study was to predict the onset of acute brucellosis depending on the activity of the inflammatory process and the development of complications. In order to reproduce the process of occurrence of both complications with associated risks, we applied a bivariate probit model. The risk of cardiovascular complications in patients with acute brucellosis of TLR-4 A/G genotype was found to be reduced by 94.67% in comparison with G/G carriers and by 56.39% among A/A genotype carriers compared to G/G genotype carriers. The risk of complications of the hepatobiliary system among carriers of the genotype G/C of the IL-6 gene compared to carriers of the genotype C/C is reduced by 10.75%.